Social skills and academic performance in psychology students - Ortiz Ochoa, William Alfredo (2018)
Social skills in the educational level allow to execute interpersonal tasks, contributing to the harmonious coexistence with others. The present study was no experimental, quantitative-correlational. The general objective was to determine the relationship between social skills and academic performance in psychology students. 424 students participated. The sample was non-probabilistic in a finite population. The instruments used were the Social Skills Scale (EHS) and the Criteria for Academic Performance of the CES. The results determined an inverse negative correlation without statistically significant association according to Pearson statistic and X2 (r = 0.073, p <0.135). In a population with ages between 20 and 16 years with (SD) 2.24 years. The level of social skills was 44.8%. The level of academic performance was very good 45.8%. It concludes that social skills are necessary for development within the university context, but are not essential to achieve good academic performance. It is recommended to continue research under this same topic in which other associated factors are explored.